New optimization feature for the developed open cnc controller based on ISO 6983 and ISO 14649 - Obayes, Noor Hatem (2021)
The computer numerical control (CNC) system controls the movement of the machine tool automatically. The development of open CNC systems is one of the most popular topics in the last three decades due to the system remains exclusive all the time. PC-based open architecture controller (OAC) has been constructed to make adding, upgrading, swapping components easy, and broke the specific vendor chain. However, this system has some limitations, such as tool path optimization. This research aims to minimize tool path airtime during machining of input ISO codes via an ant colony optimization algorithm. A new optimized system was developed based on open architecture control (OAC) technology and interpreted STEP-NC (Standard for the Exchange of Product Model Data) programming approaches. The developed system can provide a new feature for both ISO data interface models (ISO 14649 and ISO 6983) interpretation, along with its graphical verification, execution and report generation functionalities into the CNC core. The system is composed of ISO data interface models interpretation, tool path optimization, 3D simulation, and automatic document generation modules. The functionalities of the system were validated through the manufacturing of case study components. Corresponding experimental results verified the proposed technique with satisfactory outcomes. Milling and drilling with G-code and drilling with STEP-NC were evaluated on tool path optimization. The optimization process that produced the shortest tool path was observed at different solved examples. The improvement percent for G-code was 10.41% and 16.58 % for milling and drilling, respectively. While improvement percent for STEP-NC was 16.98% for drilling. The results revealed that the optimization feature has a significant effect on the tool path.